Prevalence of Neisseria gonorrhoeae infection in young subjects attending community clinics in South London. Issue 2 (27th September 2007) - Rao, G Gopal; Bacon, L; Evans, J; Dejahang, Y; Michalczyk, P; Donaldson, N
Abstract : Objectives: To describe the prevalence and epidemiology of gonococcal infection in young subjects attending community clinics in South-East London. Methods: Subjects <25 years of age participating in the National Chlamydia Screening Programme were tested for gonococcal infection using a nucleic acid amplification test (strand displacement amplification assay). Results: 10 523 tests were performed in 7369 patients (82% female) over a 2-year period in 2004 and 2005. Specimens used for tests were self-taken vulvovaginal swabs (43%), cervical swabs (40%), urine (16%) and urethral swabs (0.9%). Reasons for tests were: screening (67%), diagnosis (27%) and contacts of patients with chlamydia or gonococcus infection (7%). A significantly higher percentage of male subjects were tested as contacts (19% male vs 4% female; p<0.001). Of the 10 117 cases with definite results, 414 were positive (prevalence 4.1%, 95% CI 3.7% to 4.5%). There was a significantly higher prevalence in male subjects (5.7% male v 3.8% female; p<0.001). The average number of tests was 1.4 per patient (range 1–10). Contacts had a significantly higher prevalence (15.5%, p<0.001) than those tested for diagnostic (3.6%) or screening (3.1%) purposes. Multivariate regression analysis confirmed that there was a significantly higher prevalence in black Caribbean (5.8%, OR 2.44), black British/other black (5.6%, OR 2.33) and mixed (5.5%, OR 2.25) than white (2.4%) ethnic groups (p<0.001). Increasing age was significantly associated with lower prevalence (OR = 0.87; 95% CI 0.84 to 0.91; p<0.001). The odds of a positive test decreased by 13% for every year older. Conclusion: A community-screening programme has detected a high prevalence of Neisseria gonorrhoeae in South London, especially in teenagers, male subjects and certain ethnic groups.